2016
DOI: 10.1093/cid/ciw550
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis in Young Infants Throughout the World

Abstract: In typical pertussis in young infants, the child will appear deceptively well; he or she will have coryza, sneezing, and a mild cough. There is no fever. This progresses to gagging, gasping, eye bulging, bradycardia, cyanosis, and vomiting. There is leukocytosis with lymphocytosis and apneic episodes. Deaths relate to leukocytosis, pulmonary hypertension, and pneumonia. The source of pertussis in young infants is most often a family member with cough illness that is not recognized as pertussis. Diagnosis is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 28 publications
2
48
1
12
Order By: Relevance
“…Coughing episodes may cause brief periods of harmless apnea. Fever is not typically seen with pertussis infections, but gasping, gagging, and cyanosis are common [6]. While this patient did present with a similar paroxysmal cough, including apnea and gasping, fever was also present intermittently, setting it apart from a typical pertussis clinical vignette.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Coughing episodes may cause brief periods of harmless apnea. Fever is not typically seen with pertussis infections, but gasping, gagging, and cyanosis are common [6]. While this patient did present with a similar paroxysmal cough, including apnea and gasping, fever was also present intermittently, setting it apart from a typical pertussis clinical vignette.…”
Section: Discussionmentioning
confidence: 65%
“…Typically, this virus is spread by direct contact or close contact with secretions [6,7]. Animal models with hMPV have shown a similar pathogenic process to RSV, demonstrating viral replication in the upper respiratory tracts and prolonged airway inflammation with a continuously detectable viral RNA load.…”
Section: Discussionmentioning
confidence: 99%
“…Because IgG antibodies can cross the placenta, almost all IgG antibodies present in infants 6 months old and younger arise from the mother. A set of studies showed that when acellular pertussis vaccine was given to pregnant women in the second or third trimester, especially at 27-36 weeks of pregnancy, enough antibodies against Bacillus pertussis, such as the anti-pertussis toxin and anti-lament hemagglutinin antibodies, were detected in the blood of the neonates, and the antibodies persisted and gradually declined until completely attenuated at the age of 3 months [6,7,8]. Therefore, acellular pertussis vaccine for pregnant women could protect infants from pertussis infections before the standard age of pertussis vaccination (the age of 3 months).…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda hastaların %22,2'sinde (n=4) ateş vardı, bu hastaların 3'ünde viral enfeksiyon eşlik ediyordu. Ateş görülme sıklığı dizin ile benzerlik göstermekteydi (17,18).…”
Section: Introductionunclassified